Initial design of automated latex cup robot collector on rough terrain - Xi, Bo Khor; Yee, Chyan Tan; Chin, Jin Ong; Chong, Hooi Lim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Despite the growing demand in rubber products, the world rubber production has declined in recent years. In this paper, a prototype of an automated latex cups collecting robot is constructed to assist the workers in the latex collection process. This robot is constructed on a mobile platform with a rear-wheel drive, double wishbone suspension, Ackermann’s steer transmission, motor-driven Four Degree of Freedom (DoF) manipulator arm and a latex storage tank. Ultrasonic sensors and camera are employed to locate the position of rubber trees and latex cups. The developed prototype robot has undergone the functional test to verify the control system, in which the robot can collecting the latex cup located at the height of 105 cm and 160 cm. In the mobility test, the robot can overcome obstacles of 15 mm height. While in the static test, the platform and the robotic arm can withstand the stress in the range of 107 N/m2. In the balance test, the topple angle is more than 40°, guaranteeing the stability of the robot platform. Those results showed that the prototype design is feasible to perform basic tasks automatically in the unstructured terrain of rubber plantation.